Utilization of digital resources in grade 10 life sciences teaching and learning - Ramaila, Sam; Fakude, Siphesihle (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
This study investigated the utilization of digital resources in the context of grade 10 Life Sciences education across rural, township, and urban schools in South Africa. The research employed a mixed-method approach within an exploratory descriptive survey design, involving 50 purposefully selected participants, including grade 10 Life Sciences teachers and learners. Quantitative data were collected through the distribution of a questionnaire, while qualitative data were gathered through semi- structured interviews. The study's empirical investigation was guided by the Conceptual Framework for the Second Information Technology in Education Study (SITES) as the foundational conceptual framework. The key findings from the study revealed that the effective integration of digital technologies into grade 10 Life Sciences instruction in rural and township schools faced significant challenges primarily due to a widespread lack of resources. Additionally, it was observed that grade 10 Life Sciences teachers in selected rural and township schools exhibited a deficiency in technological pedagogical content knowledge. In contrast, teachers in urban schools demonstrated sufficient technological pedagogical content knowledge (TPACK), which facilitated the meaningful integration of digital technologies into grade 10 Life Sciences teaching and learning. Furthermore, the teachers exhibited a positive attitude towards the educational advantages of employing digital technologies as an innovative approach to achieving predefined educational objectives. The study also discusses the theoretical implications for science teaching and learning.
Journal article published in African Perspectives of Research in Teaching & Learning Vol. 7 (3) (2023)
Keywords: Digital resources; Life sciences; TPACK; Pedagogic innovation; Electronic information resources; Life sciences -- Study and teaching; Educational innovations; Educational technology